A Social Ties-based Approach to Breast Cancer Patients' Quality of Life: Examining Group Ties and Individual Ties across Offline and Online Settings. Issue 6 (12th May 2021) - Zhu, Yaguang; Glowacki, Elizabeth M.; Yang, Yin
ABSTRACT: Supportive social ties positively impact cancer patients' health; however, little is known about the intertwined links between both offline and online ties, and individual and group ties. Using the common-identity/common-bond approach, we empirically tested the critical difference that individual and group ties exert on health across offline and online settings. Results from 356 female breast cancer patients showed group ties affect quality of life through sequential group identification and social support, while individual ties affect quality of life through sequential interpersonal bonds and social support. Offline group and online individual ties are stronger predictors of quality of life than online group and offline individual ties. A cluster analysis categorized participants into four distinguishable segments. People with stronger offline interpersonal bonds and online group identification reported a better quality of life. This offers insight into the social dynamics that are most consequential for health, and the potential theoretical pathways through which they operate.